Regaining a Bright Future: Psychological Dynamics in Female Adolescent Victims of Sexual Harassment - Ajeng Nova Dumpratiwi (Gadjah Mada Journal of Psychology (GamaJoP), 2020)
Rampant sexual harassments affect the victims and need to be followed up. Victims who are majority women are likely to feel aggrieved by pregnancy, receive negative stigma from society, drop out of school, and feel unable to achieve well-being in the future. This phenomenon is the basis for research conducted with the aim of knowing the psychological dynamics and aspects that affect the psychological conditions in female adolescent victims of sexual harassment. The phenomenological approach and interview method were used in this research. Three teenage girls aged 13-18 years became informants in this study. The results showed that the psychological condition of victims of sexual harassment was influenced by who the perpetrator is or the close relationship between the victim and the perpetrator. It was also influenced by support from the social environment, especially family as the closest environment. The psychological dynamics of victims of sexual harassment are influenced by four things: 1) the attitude of the environment; 2) self-understanding ability; 3) motivation to achieve self-actualization; and 4) the attitude of comparing oneself with others who are not in a better condition. From the results of this study, it was concluded that the supporting external or environmental factors and internal process in victims of sexual harassment combined really encourage the process recovery to achieve a better future.